2011
DOI: 10.1016/j.vaccine.2011.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of H5N1 influenza vaccine viruses: Influence of internal gene segments of avian and human origin on production and hemagglutinin content

Abstract: The H5N1-clade 1 influenza vaccine strain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 37 publications
(45 reference statements)
2
29
0
Order By: Relevance
“…Retrospective analysis of seven H3N2 viruses selected as candidate vaccine strains also exhibited similar patterns of protein expression, with those containing the seasonal PB1 gene having higher HA/NP ratios, suggesting that these viruses also had higher HA protein content in virions. In addition, a similar trend of poor growth but increased HA/NP ratio was described when the PB1 of an H5N1 virus was included with its HA and NA in reverse genetics-derived H5N1 vaccine candidates containing all other genes from PR8 virus (31). Supporting our findings, a recent study (32) used cryoelectron microscopy to determine the effect of gene constellation on virion morphology.…”
Section: Discussionsupporting
confidence: 85%
“…Retrospective analysis of seven H3N2 viruses selected as candidate vaccine strains also exhibited similar patterns of protein expression, with those containing the seasonal PB1 gene having higher HA/NP ratios, suggesting that these viruses also had higher HA protein content in virions. In addition, a similar trend of poor growth but increased HA/NP ratio was described when the PB1 of an H5N1 virus was included with its HA and NA in reverse genetics-derived H5N1 vaccine candidates containing all other genes from PR8 virus (31). Supporting our findings, a recent study (32) used cryoelectron microscopy to determine the effect of gene constellation on virion morphology.…”
Section: Discussionsupporting
confidence: 85%
“…Comparison of reassortant PR8-based IVSs containing PB1 Gi (5 1 2 1 1) or the indigenous PB1 segment (5 1 3) from the donor strain of the HA/NA segments Previous studies suggested that the inclusion of the indigenous PB1 from the IAV donor strain of the HA/NA segments to be transferred into PR8-based IVSs may help to improve replication efficiency (Abt et al, 2011;Wanitchang et al, 2010). Therefore, we compared the impact of the PB1 Gi against the indigenous PB1 of H5N1/KAN and H7N9/ Anhui viruses on the replication efficiency of either the 5+2+1 or 5+3 versions of H5N1 and H7N9 subtype IVSs, respectively.…”
Section: Pb1mentioning
confidence: 99%
“…Vero cells) are increasingly being used for the production of IVSs (Hess et al, 2012;Hu et al, 2015;Huang et al, 2015;Naruse et al, 2015). In many cases, however, PR8-based reassortants containing HA and NA segments from circulating strains fail to grow efficiently in embryonated eggs and/ or cell culture, providing a significant obstacle to efficient large-scale vaccine production (Abt et al, 2011;Compans et al, 1972;Wanitchang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations